Pertumbuhan dan Hasil Jagung Pada Berbagai Pemberian Pupuk Nitrogen di Lahan Kering Regosol - Jemrifs H. H. Sonbai (Partner, 2013)
The Growth and Harvest of Corn at Variousof Providing Nitrogen Fertilizer on Regosol Dry Lands. Nitrogen is a macro-nutrient that is the primary determinant in corn crop production that is cultivated on dry land. Corn production can be increased by providing inorganic and organic fertilizer. The purpose of the research is to discover the influence of carbamide (urea fertilizer) and cow manure fertilizer levels on the growth of corn production on regosol dry land. The research was conducted from March-June, 2012, at the Gadjah Mada University (UGM) Agriculture Faculty Tridarma Garden, in Banguntapan. The experimental design uses a Complete Group Random Design (RAKL) which consists of two factors. The first factor provides three different amounts of carbamide (100 kg/ha, 150 kg/ha, and 200 kg/ha). The second factor has three different amounts of cow manure fertilizer (10 t/ha, 15 t/ha, and 20 t/ha). The research findings show that the plant height, leaf width, total plant net weight, blossom period, harvest period, seed weight, chlorophyll level, and N-leaf level are influenced by the amount of carbamide, while the amount of cow manure fertilizer can repair the physiological and chemical nature of the soil. There is no relationship between carbamide and cow manure fertilizer levels on corn growth and productivity levels. The use of carbamide has a significant influence on corn growth and productivity on regosol dry land. The average corn productivity on regosol dry land with 200 kg/ha of carbamide is 7.38 t/ha, while lamuru corn has a harvest potential of 7.6 t/ha.Key words:     Nitrogen, Cow Manure Fertilizer, Regosol Dry Land, Corn, Physiological, Growth, Harvest.